MANAJEMEN REDAKSIONAL PORTAL BERITA ONLINE DALAM MENGELOLA MEDIA SOSIAL SEBAGAI SARANA PROMOSI - Moh. Syamsul Arifin (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2018)
Social media is interactive allowing the user to consume, create content independently and distribute it in the network. With this trait, social media is utilized by personals or institutions as a means of promotion. Online media portal, Inilah.com, one of the institutions that utilizes social media to promote its news content to the public. To find out how Inilah.com work procedures in the management of redaction in the newsroom until the utilization of social media as a means of promotion that requires communication management of two different related departments, be the goal at the same time the object of this research. Qualitative descriptive method with case studies approach in this research to give description of a systematic process implementation of management redaction and communications at Inilah.com. The pattern process at Inilah.com can be one of references for other online media in running operation of online news portal. The subject of this research is the employees in the editorial (newsroom) where newsroom team produces contents and, information technology department where social media team executes content promotion. By looking at the theories of management, it can be a conclusion that Inilah.com apply the principles of management of redaction and communications in simple scale but modified in execution level to suit the company’s condition for effectiveness of the company's operations